Highly selective redistribution of primary arylsilanes to secondary arylsilanes catalyzed by Ln(CH2C6H4NMe2-o)3@SBA-15. Issue 1 (3rd December 2019) - Guo, Chenjun; Li, Min; Chen, Jue; Luo, Yunjie
Abstract : The organometallic–inorganic hybrid materials Ln(CH2 C6 H4 NMe2 - o )3 @SBA-15 (Ln = La, Y) were prepared, which demonstrated extremely high selectivity (>99%) in catalyzing the redistribution of primary arylsilanes to secondary arylsilanes. Abstract : Rare-earth metal tris(aminobenzyl) complexes Ln(CH2 C6 H4 NMe2 - o )3 (Ln = La, Y) were grafted onto the dehydroxylated periodic mesoporous silica support SBA-15 to generate the organometallic–inorganic hybrid materials Ln(CH2 C6 H4 NMe2 - o )3 @SBA-15 (Ln = La (2a ), Y (2b )), which demonstrated extremely high selectivity (>99%) in catalyzing the redistribution of primary arylsilanes to secondary arylsilanes without the requisition of strict control of the reaction conditions. The hybrid materials still showed a perfect selectivity and activity after three catalytic cycles.